The Impact of Nike Project 40/Generation Adidas Players on Major League Soccer - Carrie W. LeCrom; John P. Selwood; Philipp Daldrup; Mark Driscoll (Journal of Applied Sports Management, 2013)
Created in 1997, the Nike Project40/Generation Adidas program encourages soccer players to leave college early to sign professional contracts with Major League Soccer teams, guaranteeing them a 3-year salary with two one-year options. In theory, if the best players are being chosen to this program each year, they should be outperforming those who are drafted to MLS teams but are not a part of the program. By comparing the top draft picks within and outside the program, researchers hoped to determine whether Nike/Adidas players were having a different impact on the league than their counterparts. Results showed that, of 15 statistical categories analyzed, only three resulted in a statistically significant difference between groups. Though Nike/Adidas players were outperforming players who were not a part of the program, they were not doing so at a rate to justify the claim that they have a greater impact on the league.
Keywords: Major League Soccer; Nike Project 40; Generation Adidas; MLS SuperDraft